Analysis of the Impact of E-Money on the Money Supply in Indonesia - Nafidatul Husnia; Maulidyah Indira Hasmarini (STIE Amkop Makassar, 2026)
The rise of digital payment systems, particularly e-money, is poised to revolutionize liquidity dynamics and monetary transmission processes in Indonesia. This research seeks to dissect the impact of e-money transactions on the money supply (M2), factoring in inflation and credit card transaction values. Employing a quantitative methodology, the study draws on monthly time series data from 2022 to 2024, sourced from Bank Indonesia and the Central Statistical Agency. The analytical framework is grounded in multiple linear regression utilizing Ordinary Least Squares (OLS), alongside classical assumption testing to ensure valid estimations. The findings reveal that e-money exerts a positive and significant influence on the money supply, whereas credit card transactions show a negative and significant impact, and inflation does not yield any significant effect. These results underscore a transformation in money supply dynamics, increasingly shaped by shifts in transaction behavior and the heightened utilization of digital payment tools, in contrast to traditional monetary influences. This signifies a realignment in monetary transmission mechanisms, where liquidity now reflects not only inflationary pressures but also the velocity of money circulation propelled by the digitization of payments. The policy implications highlight the necessity of weaving the advancement of digital payment systems into the fabric of monetary policy formulation and liquidity management.